Distal Biceps Brachii Tendon Repairs: A Single-Incision Technique Using a Cortical Button With Interference Screw Versus a Double-Incision Technique Using Suture Fixation Through Bone Tunnels. (May 2015) - Shields, Edward; Olsen, Joshua R.; Williams, Richard B.; Rouse, Lucien; Maloney, Michael; Voloshin, Ilya
Background: Distal biceps brachii tendon repairs performed with a tension slide technique using a cortical button (CB) and interference screw are stronger than those based on suture fixation through bone tunnels (BTs) in biomechanical studies. However, clinical comparison of these 2 techniques is lacking in the literature. Purpose: To perform a clinical comparison of the single-incision CB and double-incision BT techniques. Study Design: Cohort study; Level of evidence, 3. Methods: Distal biceps tendon ruptures repaired through either the single-incision CB or double-incision BT technique were retrospectively identified at a single institution. Patients >1 year out from surgery were assessed for range of motion, strength, and complications, and they completed a DASH questionnaire (Disabilities of the Arm, Shoulder, and Hand). Results: Patients in the CB group (n = 20) were older (52 ± 9.5 vs 43.7 ± 8.7 years; P = .008), had a shorter interval from surgery to evaluation (17.7 ± 5 vs 30.8 ± 16.5 months; P = .001), and were less likely to smoke (0% vs 28.5%; P = .02) compared with the BT patients (n = 21). DASH scores were similar between groups (4.46 ± 4.4 [CB] vs 5.7 ± 7.5 [BT]; P = .65). Multivariate analysis revealed no differences in range of motion or strength between groups. More CB patients (30%; n = 6) experienced a complication compared with those in the BT group (4.8%; n = 1) ( P = .04), and these complications were predominantly paresthesias of the superficial radial nerve that did not resolve. There were no reoperations or repair failures in either group. Conclusion: Both the single-incision CB and double-incision BT techniques provided excellent clinical results. Complications were more common in the single-incision CB group and most commonly involved paresthesias of the superficial radial nerve.